Falasha: Peradaban Yahudi di Etiopia dan Kekerasan atas Nama Agama - Sembiring, William Wahyu (JURNAL TERUNA BHAKTI, 2023)
Africa and Judaism are two things that are rarely discussed in the world of church history in Indonesia. The purpose of writing this article is to understand comprehensively and briefly the Jewish civilization in Ethiopia to see the problem of violence that arises when Jews meet Christians in Africa. The Jews in Ethiopia experienced persecution because of differences in religion and culture, and the perpetrators of the persecution were the state and the Christians in power. This study uses a qualitative method by looking at and comparing several written sources as a reference in explaining the historical situation that occurred. The result of this paper is that religion provides legitimacy for violence in achieving political power.  AbstrakAfrika dan Yahudi adalah dua hal yang jarang diperbincangkan dalam dunia sejarah gereja di Indonesia. Tujuan dari penulisan artikel ini adalah memahami secara komprehensif dan ringkas mengenai peradaban Yahudi di Etiopia, guna melihat masalah kekerasan yang muncul ketika Yahudi bertemu dengan Kristen di Afrika. Orang-orang Yahudi di Etiopia mengalami persekusi oleh karena perbedaan agama dan kebudayaan, dan pelaku dari persekusi itu adalah negara dan orang-orang Kristen yang berkuasa. Penelitian ini menggunakan metode kualitatif-historis dengan melihat serta membandingkan beberapa sumber tulisan sebagai acuan memaparkan situasi sejarah yang terjadi. Hasil dari tulisan ini adalah agama memberikan legitimasi kekerasan dalam mencapai kekuasaan politik.